Hybrid functional IrO2-TiO2 thin film resistor prepared by atomic layer deposition for thermal inkjet printheads - KWACK, Won-Sub; MOON, Hyoung-Seok; JEONG, Seong-Jun; WANG, Qi-min; Kwon, Se-Hun (Transactions of Nonferrous Metals Society of China, 2011)
IrO2-TiO2 thin films were prepared by atomic layer deposition using Ir（EtCp）（COD） and titanium isopropoxide （TTIP）. The resistivity of IrO2-TiO2 thin films can be easily controlled from 1 500 to 356.7 μΩ·cm by the IrO2 intermixing ratio from 0.55 to 0.78 in the IrO2-TiO2 thin films. The low temperature coefficient of resistance（TCR） values can be obtained by adopting IrO2-TiO2 composite thin films. Moreover, the change in the resistivity of IrO2-TiO2 thin films was below 10% even after O2 annealing process at 600 ℃. The step stress test results show that IrO2-TiO2 films have better characteristics than conventional TaN08 heater resistor. Therefore, IrO2-TiO2 composite thin films can be used as a heater resistor material in thermal inkjet printhead.